The beneficial role of the VAST Challenges in the evolution of GeoTime and nSpace2. (January 2015) - Proulx, Pascale; Canfield, Casey
Oculus participated in the first VAST Challenge in 2006 and in every subsequent year except one. Although we have won 5 awards in the last 7 years, they are not the main reason we spend much time and effort preparing our submission each year. The VAST Challenge has proven to be a valuable exercise in evaluating and refining our tools and our thinking. No organization that has the desire to create the best possible analytic tools should pass by the unique opportunity to work on a realistic set of tasks, against nontoy datasets containing ground truth, and to be evaluated by both senior analysts and experts within the visual analytics community. Oculus staff and products have benefited from the experience as have the whole visual analytics community researchers and practitioners.